PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR SISWA - Arlinah, Euis Ani (Universitas Negeri Semarang, 2021)
The inability of most students to solve a problem shows that students do not understand the concepts taught by the teacher in learning activities, the skills to solve a problem individually and collaboratively, students need to be directed to an understanding, one of which is by determining the learning model, the cooperative learning model type Think Pair Share (TPS) is a learning model that can increase the effectiveness of students' psychomotor learning. The results showed that: (a) most of the students gave a positive response to the application of the TPS type cooperative learning model, (b) the results of observations showed that most of the students could be active in the learning process, (c) the results of the formative and summative tests showed that the students experience an increased level of completeness, (d) the TPS type cooperative learning model can increase student learning activities and mastery. Ketidakmampuan sebagian besar siswa dalam memecahkan suatu permasalahan memperlihatkan bahwa siswa belum memahami konsep yang diajarkan guru dalam kegiatan pembelajaran, keterampilan memecahkan suatu permasalahan secara individu dan bekerjasama, siswa perlu diarahkan kepada suatu pemahaman, salah satunya dengan menentukan model pembelajaran, model pembelajaran kooperatif tipe Think Pair Share (TPS) merupakan sebuah model pembelajaran yang dapat meningkatkan efektivitas belajar psikomotorik siswa. Hasil penelitian menunjukkan bahwa : (a) sebagian besar siswa memberikan respon yang positif terhadap penerapan model pembelajaran kooperatif tipe TPS, (b) hasil observasi menunjukkan sebagian besar siswa dapat beraktivitas dalam proses pembelajaran, (c) hasil tes formatif dan tes sumatif menunjukkan bahwa siswa mengalami tingkat ketuntasan yang meningkat, (d) model pembelajaran kooperatif tipe TPS dapat meningkatkan aktivitas dan ketuntasan belajar siswa.